Cr(VI) ions removal from aqueous solutions using carrot residues as an adsorbent / Mohd Izuddin Nuzul and Siti Kartina Abdul Karim - Nuzul, Mohd Izuddin; Abdul Karim, Siti Kartina (Universiti Teknologi MARA, 2019)
The aims of this study were to characterize carrot residues and to determine the removal of Cr(VI) in water depending on the temperature and the dosage of carrot residues. To identify the functional group present in carrot residue, Fourier-Transform Infrared (FTIR) was used to characterize it. The functional group that responsible for the metal binding is hydroxyl (-OH) group. The adsorption of Cr(VI) was conducted by using batch experiment. The effect of temperature and dosage were studied in batch experiment, in which temperatures were varied from 25ºC to 55ºC and the dosages were varied from 0.5 mg/L to 2 mg/L. Preliminary study was done to determine the time equilibrium for adsorption. The equilibrium contact time was 30 min with 12.66% removal efficiency. Meanwhile, the highest dosage for removal efficiency of metal that used was 2 mg/L with 13.09%. The optimum temperature was 25ºC with 12.66% removal efficiency. This study has indicated that the carrot residues is less likely a good adsorbent for removal of Cr(VI).